2019
DOI: 10.1038/s41598-019-42428-y
|View full text |Cite
|
Sign up to set email alerts
|

The development of a high-density genetic map significantly improves the quality of reference genome assemblies for rose

Abstract: Roses are important woody plants featuring a set of important traits that cannot be investigated in traditional model plants. Here, we used the restriction-site associated DNA sequencing (RAD-seq) technology to develop a high-density linkage map of the backcross progeny (BC1F1) between Rosa chinensis ‘Old Blush’ (OB) and R. wichuraiana ‘Basyes’ Thornless’ (BT). We obtained 643.63 million pair-end reads and identified 139,834 polymorphic tags that were distributed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 60 publications
0
20
2
Order By: Relevance
“…The collinearity between the assembled BT chromosome sequences and the K5 genetic map (Bourke et al, 2018) was very high with most of the association efficiency above 95% (Supplementary Table S8; Supplementary Figure S3). Except chromosome in the OBxBT genetic map, on which the distribution of molecular markers was obviously skewed (Li et al, 2019c), all the other 6 chromosomes showed a very good collinearity with correlation rate around 90% (Supplementary Figure S4; Supplementary Table S8). We next aligned our BT assembly to the recently reported haploOB genome sequences (Hibrand Saint-Oyant et al, 2018;Raymond et al, 2018) and identified a very high collinearity of BT assembly to both Raymond's (Figure 2A,2B) and Hibrand Saint-Oyant's (Supplementary Figure S3) genomes, revealing a high synteny level and gene order between these two genotypes.…”
Section: Bt Genome Is In Reference-quality With High Completenessmentioning
confidence: 99%
See 4 more Smart Citations
“…The collinearity between the assembled BT chromosome sequences and the K5 genetic map (Bourke et al, 2018) was very high with most of the association efficiency above 95% (Supplementary Table S8; Supplementary Figure S3). Except chromosome in the OBxBT genetic map, on which the distribution of molecular markers was obviously skewed (Li et al, 2019c), all the other 6 chromosomes showed a very good collinearity with correlation rate around 90% (Supplementary Figure S4; Supplementary Table S8). We next aligned our BT assembly to the recently reported haploOB genome sequences (Hibrand Saint-Oyant et al, 2018;Raymond et al, 2018) and identified a very high collinearity of BT assembly to both Raymond's (Figure 2A,2B) and Hibrand Saint-Oyant's (Supplementary Figure S3) genomes, revealing a high synteny level and gene order between these two genotypes.…”
Section: Bt Genome Is In Reference-quality With High Completenessmentioning
confidence: 99%
“…To understand the genetic pattern of stem prickle density, we scored stem prickle density in the 99-individual F1 and the 148-individual BC1F1 populations generated via crossing the prickleless BT and prickly OB ( Figure 3A; supplementary Figure S17-S19) (Li et al, 2019c;Li et al, 2015). In the F1 population, the number of prickleless vs. prickly individuals is 13:86, a ratio not deviating from 1:7 (three loci hypothesis, Chi-square test, p=0.96) or 1:15 (four loci hypothesis, Chi-square test, p=0.43).…”
Section: Genetic Patterning Of Stem Prickle Density In Bt X Ob Populamentioning
confidence: 99%
See 3 more Smart Citations